Passionvine Mealybug, Planococcus minor (Maskell) (Hemiptera: Pseudococcidae) - Antonio W. Francis; Moses T. K. Kairo; Amy L. Roda (EDIS)
The passionvine mealybug was discovered in the continental U.S. for the first time in southern Florida a little over a year ago. USDA, APHIS lists it as a high priority threat. Given its polyphagous nature, this pest should be given careful attention in a new area such as Florida, which has an important agricultural sector and amenable climate. This 6-page fact sheet was written by Antonio W. Francis, Moses T. K. Kairo, and Amy L. Roda, and published by the UF Department of Entomology and Nematology, February 2012.